Procedure for Obtaining a Certificate of Title to the Land in the Semarang: Case Study in the National Land Agency Semarang - Niken Windy Ika Pratiwi; Munawwarah Munawwarah; Munsharif Abdul Chalim (Jurnal Akta, 2019)
The background of this thesis-making by the problems that occur in the community, where people are still not or do not understand the procedures milik.Terbukti acquire rights to their land dispute or a state-owned building that happened because the people who inhabit this land are not applying for property rights and feel that the land itself. Scription this is made so that people understand about the procedures for securing property rights. Results: (1) Procedures of obtaining the certificate is property rights on state land through the National Land Agency, is generally set in the norm of the Minister of Agriculture No. 9 of 1999 on Procedures for Granting and Cancellation of State Land Property Rights and Rights Management. In Article 19 paragraph (2) BAL consisting of: bookkeeping land, registration of property rights, transfer of land rights, granting letters of proof of receipt of rights, (2) Barriers and solusiyang arising from applicant in the application process right (external): lack of accessories the proposed requirements of the applicant, not terselesainya application fee, the land dispute would be applied. Barriers arising from the Office of the (internal): lack of personnel in the service of the applicant carefully situations, employees who lack discipline, negligence of officers in performing their duties. Solution resistance of the applicant (external): more thoroughly before entering the application requirements, before making an application should first ask for details of funds in the process of granting the right, please check whether the land is in sengeketa or not. Solution barriers of Office (internal): officers should be more responsible in performing their duties, and provide a deterrent effect to employees who are lazy in performing their duties.Keywords: Procedures; Certificate of Property Rights; State land.